Influence of cytokinins and yeast extract on growth and flavone production in hairy root cultures of Scutellaria baicalensis - Kwon, Haejin; Kim, Haeng-Hoon; Choi, Minsol; Nguyen, Bao Van; Kim, Kihyun; Kim, Jae Kwang; Park, Sang Un (Journal of Phytology, 2023)
Hairy roots produce various bioactive chemical compounds than wild-type roots which offer a promising in vitro approach for synthesizing important nutraceutical compounds. The purpose of this study is to increase the production of flavone compounds in hairy root cultures of Scutellaria baicalensis by the addition of elicitors such as cytokinins and yeast extract. Cytokinins such as kinetin (KIN), 6-benzylaminopurine (BAP), and Thidiazuron (TDZ) were utilized at 0.1, 0.5, and 1.0 mg/L, whereas for yeast extract treatment 50, 100, and 150 mg/L concentrations were added to the ½ SH medium. Effects of elicitors were measured in terms of dry biomass and flavone contents (baicalin, baicalein, and wogonin) using high-performance liquid chromatography (HPLC). The highest dry weight was achieved in the control hairy root than that of all cytokinins-treated hairy root cultures. In all the cytokinin-treated hairy root cultures, as the concentration increased the dry weight of the hairy root decreased. In contrast, in all the yeast extract-treated hairy root cultures as the concentration increases the dry weight of the hairy root increased, whereas the highest dry weight was achieved in 150 mg/L of yeast extract. Moving to the flavone content, baicalin was detected highest content in all the hairy root cultures supplied with cytokinin and yeast extract. The highest total flavone content was achieved in the hairy root culture treated with 1.0 mg/L of TDZ and 50 mg/L of yeast extract. This result might help the commercial agronomic sector by facilitating the in vitro mass production of nutraceuticals using S. baicalensis hairy root cultures.